Monitoring ecological impacts : concepts and practice in flowing waters - Downes, Barbara J., 1958- (Cambridge University Press, 2002)
Monitoring Ecological Impacts provides the tools needed to design assessment programs that can reliably monitor, detect and allow management of human impacts on the natural environment. The procedures described are well-grounded in inferential logic. Step-by-step guidelines and flow diagrams provide clear and useable protocols, which are applicable to real situations.